RATIO LEGIS OF THE CONSTITUTIONAL COURT DECISION ABOUT IMPEACHMENT: IS IT FINAL AND BINDING? - Khamim Muhammad Ma'rifatulloh (Faculty of Law, University of Muhammadiyah Malang, 2019)
Arrangement of the final and binding legal force ‎the decisions of the Constitutional Court's impeachment not previously regulated in legislation. After PMK No 21 Year 21 Year 2009 paragraph (5) is issued, it also raises legal problems related to its material content. The formulation of the research problem is what ratio legislation Constitutional Court No. 21 of 2009 Article 19 Paragraph (5) About Impeachment. This research is a normative juridical approach with a statutory approach, a conceptual approach. The results of this study are to fill in the gaps or incomplete arrangements for the final nature and tie the decisions of the Constitutional Court's impeachment which were previously not in the legislation.